Quark transverse spin-momentum correlation of the nucleon from lattice QCD: the Boer-Mulders function - The Lattice Parton collaboration; Lingquan Ma; Jun Hua; Andreas Schäfer; Hai-Tao Shu; Yushan Su; Peng Sun; Lisa Walter; Wei Wang; Xiaonu Xiong; Yi-Bo Yang; Jian-Hui Zhang; et al. (Journal of High Energy Physics)
Abstract We present the first lattice QCD calculation of the quark transverse spin-momentum correlation, i.e., the naive time-reversal-odd Boer-Mulders function, of the nucleon, using large-momentum effective theory (LaMET). The calculation is carried out on an ensemble with lattice spacing a = 0.098 fm and pion mass 338 MeV, at various proton momenta up to 2.11 GeV. We have implemented perturbative matching up to the next-to-next-to-leading order together with a renormalization-group resummation improvement. The result exhibits the expected decay behavior with increasing transverse separation b ⊥. We also compare the results in the nucleon and pion.